(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Intestinal obstruction in children is a disorder of faecal obstruction in the GI tract caused by mechanical obstruction, innervation disorders or a combination of these factors. The disease manifests with severe pain syndrome, indomitable vomiting, and delayed defecation and gas retention. Diagnostic search includes physical examination of the child, the use of instrumental methods - review radiography of the abdominal cavity, sonography, laparoscopy. Treatment consists of intestinal decompression and prescription of medications, in case of ineffectiveness of which surgical intervention is performed.